The Development of Trilingual Picture Dictionary for Elementary Students - Desrin Lebagi; Moh. Abraham Akbar Eisenring; Dwi Putri; Riskayani, Riskayani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Currently, schools are encouraged to incorporate local content into learning activities. However, in some remote areas, the availability of supporting teaching materials remains limited, creating a challenge to effective implementation. Therefore, this study aims to develop a trilingual picture dictionary designed for elementary students to enhance their vocabulary acquisition and language skills in three languages: English, Bahasa Indonesia, and Pamona. The dictionary serves as an educational tool to support multilingual education by providing visual aids and culturally relevant content that is accessible to young learners. A research and development (R&D) approach was employed, incorporating the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model to systematically create and refine the dictionary. The stages of analysis, design, and development have been conducted, including the selection of eight themes, which were subsequently developed into a trilingual picture dictionary. However, the remaining steps of the model will be done in following research in the future.